2014
DOI: 10.25011/cim.v37i1.20865
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol prevents methotrexate-induced renal oxidative injury and renal damage in rats

Abstract: TurkeyCarvacrol prevents methotrexateinduced renal oxidative injury and renal damage in rats AbstractPurpose: e purpose of this study was to investigate the e ect of carvacrol (CAR) on methotrexate (MTX)-induced renal damage in rats.Methods: Twenty-four male rats were equally divided into three groups: group I, control treatment; group II, MTX-treated; and group III, MTX+CAR-treated. A single dose of CAR (73 mg/kg) was administered intraperitoneally to group III on the rst day of the experiment and a single do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…dose of 20 mg/kg as previously described in certain tissue toxicity studies. 11,25 Although the exact mechanisms of MTX-associated nephrotoxicity have not been clearly understood, recent studies suggest that it may be due to oxidative stress. 26 QE is a very potent anti-oxidant providing protection against oxidative injury through prevention of the formation of hydroxyl radicals via Fe and Cu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…dose of 20 mg/kg as previously described in certain tissue toxicity studies. 11,25 Although the exact mechanisms of MTX-associated nephrotoxicity have not been clearly understood, recent studies suggest that it may be due to oxidative stress. 26 QE is a very potent anti-oxidant providing protection against oxidative injury through prevention of the formation of hydroxyl radicals via Fe and Cu.…”
Section: Discussionmentioning
confidence: 99%
“…Dosage of MTX was determined from those described by relevant literatures. [11][12][13] The dose of QE was decided based on a recent study reported by Aktoz et al 14…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…with a single dose of 20 mg/kg of Mtx (Avadi et al, 2011;Bozkurt et al, 2014) and given corn oil by oral gavage (o.g).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Toxicity from oxidative injury was recently shown to be prevented or alleviated by herbal compounds with antioxidative activity (Dalaklioglu et al, 2013;Bozkurt et al, 2014;Ali et al, 2014). Resveratrol may have a protective effect against MTX-induced hepatotoxicity by blocking oxidative stress-mediated lipid peroxidation (Dalaklioglu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%